(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article analyzes the reform of preschool education and the problem of formation and psychological features of national traditions and values in the moral education of children of preschool age on the basis of scientific, theoretical, methodological, socio-political sources, analysis of the current situation in practice. It describes how to identify and justify the relationship between the concept of moral behavior in preschool children and the psychological and social moral characteristics of children.